Circus and the avant-gardes history, imaginary, innovation - Jürgens, Anna-Sophie; Hildbrand, Mirjam (Routledge, Taylor & Francis Group, 2022)
"This book examines how circus and circus imaginary have shaped the historical avant-gardes at the beginning of the 20th century and the cultures they help constitute, to what extent this is a mutual shaping, and why this is still relevant today. This book aims to produce a better sense of the artistic work and cultural achievements that have emerged from the interplay of circus and avant-garde artists and projects, and to clarify both their transhistorical and trans-medial presence, and their scope for interdisciplinary expansion. Across 14 chapters written by leading scholars - from fields as varied as circus, theatre and performance studies, art, media studies, film and cultural history - some of which are written together with performers and circus practitioners, the book examines to what extent circus and avant-garde connections contribute to a better understanding of early 20th century artistic movements and their enduring legacy, of the history of popular entertainment, and the cultural relevance of circus arts. Circus and the Avant-Gardes elucidates how the realm of the circus as a model, or rather a blueprint for modernist experiment, innovation and (re)negotiation of bodies, has become fully integrated in our ways of perceiving avant-gardes today. The book does not only map the significance of circus/avant-garde phenomena for the past, but, through an exploration of their contemporary actualisations (in different media), also carves out their achievements, relevance, and impact, both cultural and aesthetic, on the present time."--
Keywords: Geschichte 1900-2000; Darstellende Kunst; Zirkus; Avantgarde; Circus / History / 20th century; Avant-garde (Aesthetics) / History / 20th century; Cirque / Histoire / 20e siècle; Avant-garde (Aesthetics); Circus; 1900-1999; History; Aufsatzsammlung